Significance of Adenosine Deaminase in Diagnosing Tuberculous Pleural Effusion in Nepalgunj Medical College Teaching Hospital Kohalpur - Shyam, B.K.; Shah, Sujeet Kumar; Pandey, Sumit; Baral, Sushil; Gupta, Sandeep (Journal of Nepalgunj Medical College, 2017)
Background: Tuberculosis (TB) is a major public health problem in developing countries including Nepal. One of the common presentations of TB is pleural effusion. The diagnosis of tubercular pleural effusion can be difficult because of the low rate of detecting tubercular bacilli by direct stain and culture of pleural fluid for acid-fast bacilli (AFB). Pleural biopsy can be useful but is invasive and requires experts. In this context, pleural fluid Adenosine Deaminase (ADA) level has been proposed as easy, cheap and highly sensitive test for diagnosis of TB pleural effusion. Objectives: The present study was undertaken to define the role of pleural fluid ADA value in accurate diagnosis of Tubercular pleural effusion. Methods: A Prospective analysis of 68 patients admitted in Nepalgunj Medical College teaching Hospital was done from January 2014 to December 2015 with pleural effusion. Pleural fluid ADA level was evaluated in all patients, and significance of pleural fluid ADA level in TB pleural effusion was studied. Results: Age of patients were between 20 to 80 years, with the minimum being 20 years and maximum being 79 years. In this study 85% of cases had pleural effusion due to tuberculosis. Out of the 68 patients with pleural effusion, 58(85%) were finally diagnosed to be due to tuberculosis, 2 were diagnosed to be due to malignancy, 4 due to pneumonia leading to parapneumonic effusion, 1 due to congestive heart failure and 3 due to nephrotic syndrome. Conclusion: It is difficult to diagnose TB pleural effusion by other conventional methods, as it has also been shown in our study also. Previous literatures have also mentioned AFB detection rate to be low from pleural fluid sample. Determination of ADA is a cheap and easy test which we now consider in the early routine evaluation of patients with pleural effusions, particularly if diagnosis of tuberculosis is suspected and in places where prevalence of the disease is still high as is in our country. The other method considered for diagnosing TB pleural effusion is pleural biopsy which is invasive blind procedure and requires high expertise as well. JNGMC Vol. 14 No. 1 July 2016